Microbiological Quality of Three Freshwater Fish Species from Two Local Markets in Region 6, (Corentyne, East Berbice) Guyana - Giddings, Calvin Devin; Ansari, Abdullah Adil; Silva, Phillip Da (The Asia Journal of Applied Microbiology, 2015)
Present case study was carried out during 2013, to assess the microbiological quality of three freshwater fishes (Hoplosternum littorale, Cichlasoma bimaculatum and Hoplias malabaricus) offered for sale at two local markets in region 6. Fishes were examined for microbial quality and compared to the recommended levels of U.S Food and Drug Association (FDA) and Environmental Protection Agency (EPA) for fish and fisheries product. The results revealed based on the statistical test CHI-SQAURE that the microbial levels for the three freshwater fishes deviated significantly from U.S FDA and EPA expected standard. ANOVA done on the results further showed that there was no significant difference in coliform level among fish species and markets and for E. coli level, there was also no significant difference except at p<0.01. In conclusion, the three freshwater fishes offered for sale at local markets were not of acceptable standard based on U.S FDA and EPA Acceptable level and thus implores risk to human health.